Media-Induced Secondary Traumatic Stress: The Case of the Kahramanmaras Earthquake in Turkey - Selin Kiraz Demir; Nur İnci Namli (European Journal of Mental Health)
Introduction: Trauma manifests in a variety of ways and disrupts the lives of individuals. This is particularly the case in an age when communication technologies are permeating everyday practices, and mass media is an essential means of communication. A review of the international literature on disasters reveals that the measurement tools used in the research on the association between Secondary Traumatic Stress (STS) and the media are limited.